2018
DOI: 10.1002/jcb.26602
|View full text |Cite
|
Sign up to set email alerts
|

2,5‐hexanedione induces bone marrow mesenchymal stem cell apoptosis via inhibition of Akt/Bad signal pathway

Abstract: 2,5-Hexanedione (HD) is an important bioactive metabolite of n-hexane and mediates the neurotoxicity of parent compound. Studies show that HD induces apoptotic death of neural progenitor cells. However, its underlying mechanism remains unknown. Mesenchymal stem cells (MSCs) are multipotential stem cells with the ability to differentiate into various cell types and have been used as cell model for studying the toxic effects of chemicals on stem cells. In this study, we exposed rat bone marrow MSCs to 0, 10, 20,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Moreover, the major metabolite 2,5-hexanedione of the organic solvent n-hexane, which is widely used in adhesive preparation, paints, varnishes, oil-based paint, and the food industry, can induce apoptosis of BMSCs via the mitochondria-mediated caspase-3 pathway [Sun et al, 2018;Chen et al, 2015] and nervous lesions [Cui et al, 2007]. Some chemotherapy drugs, such as arsenic trioxide, which significantly inhibited acute leukemia cells, induced mesenchymal stem cell (MSC) apoptosis through the mitochondria-mediated caspase-3 pathway in the patient's body [Cai et al, 2010].…”
Section: The Apoptosis Of Stem Cells Plays An Important Role In Variomentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the major metabolite 2,5-hexanedione of the organic solvent n-hexane, which is widely used in adhesive preparation, paints, varnishes, oil-based paint, and the food industry, can induce apoptosis of BMSCs via the mitochondria-mediated caspase-3 pathway [Sun et al, 2018;Chen et al, 2015] and nervous lesions [Cui et al, 2007]. Some chemotherapy drugs, such as arsenic trioxide, which significantly inhibited acute leukemia cells, induced mesenchymal stem cell (MSC) apoptosis through the mitochondria-mediated caspase-3 pathway in the patient's body [Cai et al, 2010].…”
Section: The Apoptosis Of Stem Cells Plays An Important Role In Variomentioning
confidence: 99%
“…In the process of apoptosis, the cell elastic modulus and volume significantly decreased, and the cell surface roughness obviously increased; subsequently, the early apoptosis marker PS was detected, eventually the cells died. In combination with the previous molecular mechanism of stem cell apoptosis [Tower, 2015;Liu et al, 2018;Sun et al, 2018;Chen et al, 2015;Cui, 2007], stem cell apoptosis is not only a biological apoptotic signal cascade process, but is also accompanied by the reconstruction of mechanics and nanomorphology. These findings were helpful for further understanding and mastering the apoptosis of cells from the perspective of mechanics.…”
Section: Biology Open • Accepted Manuscriptmentioning
confidence: 99%
“…The relative ratio of green to red fluorescence was significantly increased in experimental groups, suggesting that α -mangostin caused MMP in MG-63 cells to collapse ( Figure 3(b) ). The loss of MMT results in the translocation of cytochrome c from mitochondria into cytosol [ 25 ]. As shown in Figure 3(c) , treatment with α -mangostin 25 μ M significantly increased the release of cytochrome c into the cytosol.…”
Section: Resultsmentioning
confidence: 99%
“…In the process of apoptosis, the cell elastic modulus and volume significantly decreased, and the cell surface roughness obviously increased; subsequently, the early apoptosis marker PS was detected, eventually the cells died. In combination with the previous molecular mechanism of stem cell apoptosis [Tower, 2015; Liu et al, 2018; Sun et al, 2018; Chen et al, 2015; Cui, 2007], stem cell apoptosis is not only a biological apoptotic signal cascade process, but is also accompanied by the modification of cell mechanics and nanomorphology. This study is helpful for further understanding and mastering the apoptosis of cells from the perspective of mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that radiation induced apoptosis of BMSCs through mir-22-exotrophic stress, which affected the repair and regeneration of bone tissue in irradiated sites [Liu et al, 2018]. Moreover, the major metabolite 2,5-hexanedione of the organic solvent n-hexane, which is widely used in adhesive preparation, paints, varnishes, oil-based paint, and the food industry, can induce apoptosis of BMSCs via the mitochondria-mediated caspase-3 pathway [Sun et al, 2018; Chen et al, 2015] and nervous lesions [Cui et al, 2007]. Some chemotherapy drugs, such as arsenic trioxide, which significantly inhibited acute leukemia cells, induced mesenchymal stem cell (MSC) apoptosis through the mitochondria-mediated caspase-3 pathway in the patient’s body [Cai et al, 2010].…”
Section: Introductionmentioning
confidence: 99%